Question:

Hi! How do you solve this: a - 4 [b - 2(c - x)] = 6 for x? ?

by  |  earlier

0 LIKES UnLike

Solve the equation for x.

a - 4 [b - 2(c - x)] = 6

Please explain how you get this, my book is not good at explaining and doesn't even have an example.

Thanks! 10 pts for clearest answer. :)

Cheers.

 Tags:

   Report

8 ANSWERS


  1. a - 4 [b - 2(c - x)] = 6

    a - 4 [b - 2c + 2x] = 6

    a - 4b + 8c - 8x = 6

    -8x = 6 - a + 4b -8c

    x = a/8 - b/2 +c - 3/4


  2. a - 4 [b - 2(c - x)] = 6

    a - 4 [b - 2c + 2x)] = 6

    a - 4b +8c -8x = 6

    -8x = 6-a+4b-8c-8

    x = (6-a+4b-8c-8)/-8


  3. x= a/8 - b/2 + c - 3/4

    given:

    a - 4 [b - 2(c - x)] = 6

    distribute the -4 (remember, two negatives cancel):

    a - 4b + 8(c - x) = 6

    distribute the 8:

    a - 4b + 8c - 8x = 6

    subtract 6 from both sides:

    a - 4b + 8c - 8x - 6 = 0

    add 8x to both sides (to move the 8x to the right):

    a - 4b + 8c - 6 = 8x

    divide everything by 8:

    a/8 - 4b/8 + 8c/8 - 6/8 = x

    simplify:

    a/8 - b/2 + c - 3/4 = x

  4. solution...

    a - 4 [b - 2(c - x)] = 6

    (1) a - 4 [b - 2c -2x] = 6 ----->distribute the values from the inner most.

         a - 4b - 8c - 8x = 6

    (2) -8x = 6 - (a - 4b - 8c) ------>transpose all the values expect x, if the                       value of x is negative then multiply both sides by -1.

          8x = a - 4b - 8c - 6

    (3) x = (a - 4b - 8c -6) / 8 ----->divide the right side by the 8 so that the x will now remain.

    (4) x = (a/8) - (b/2) - (c) - (3/4)----->the value of x, if a,b and c are constant values.

    well, that the way i solve it...

  5. Well. You have to distribute all the coefficients in the parenthesis. I'll take it step by step from here.

    1. Distribution

    a - 4(b - 2c - 2x) = 6

    2. Distribution (again)

    a - 4b - 8c - 8x = 6

    3. From here, you want to isolate 'x' by subtracting and adding terms. You end up getting:

    8x = a - 4b - 8c - 6

    4. Divide by 8 to get x by itself

    x = (a - 4b - 8c - 6) / 8

    And that's it. Basically, all you want to do is get the variable you're solving for out of any parentheses, and then isolate it (get it on one side of the = sign, and everything else on the other side), and then solve for x.

  6. a - 4 [b - 2(c - x)] = 6

    multiply it out

    a - 4 [b - 2c + 2x] = 6

    a - 4b + 8c - 8x = 6

    a - 4b + 8c - 8x - 6 = 0

    move x to right side, everything else to left

    a - 4b + 8c - 6 = 8x

    swap sides and divide by 8

    x = (1/8)(a - 4b + 8c - 6)

    .


  7. a - 4 [b - 2(c - x)] = 6

    step 1: expand all brackets

    a - 4 [b - 2c + 2x] = 6

    a - 4b + 8c - 8x = 6

    step 2: subtract 6 from both sides

    a - 4b + 8c - 8x - 6 = 0

    step 3: add 8x to both sides

    a - 4b + 8c - 6 = 8x

    or

    8x = a - 4b + 8c - 6

    step 4: divide by 8

    x = (a - 4b + 8c - 6) / 8

  8. a - 4 [b - 2(c - x)] = 6

    First, do the multiplication in ( ) brackets first.

    a - 4 [b - 2c + 2x] = 6

    Now, do the multiplication in [ ] brackets.

    a - 4b + 8c - 8x = 6

    To solve for x, put x on one side and the other variables or numbers on the other side.

    a - 4b + 8c - 6 = 8x

    => 8x = a - 4b + 8c - 6

    => x = (a - 4b + 8c - 6) / 8

Question Stats

Latest activity: earlier.
This question has 8 answers.

BECOME A GUIDE

Share your knowledge and help people by answering questions.